Seasonal changes in reindeer physiology - Pösö, A. Reeta (Rangifer, 2005)
The seasonal changes in the photoperiod, temperature and availability of food need to be converted to hormonal signals in order to induce adaptations in the physiology of the reindeer. The most reliable of the seasonal changes in the environment is the photoperiod, which affects the reindeer physiology through pineal gland and its hormone, melatonin. Usually there are large diurnal changes in the concentration of melatonin, but in the reindeer the daily rhythm disappears during the arctic summer to return again in the autumn. Seasonal changes in melatonin secretion are involved in the regulation of reproduction, the growth of pelage, thermogenesis, body mass and immune function. Melatonin may exert its effects through gene activation, but the mechanisms are not completely understood. Other hormones that show seasonality are thyroid hormones, insulin and leptin. Thus the observed physiological changes are a result of actions of several hormones. Appetite, energy production and thermogenesis are all vital for survival. During winter, when energy balance is negative, the reindeer uses mainly body fat for energy production. The use of fat stores is economical as the rate of lipolysis is controlled and the use of fatty acids in tissues such as muscle decreases. Only in severe starvation the rate of lipolysis increases enough to give rise to accumulation of ketone bodies. The protein mass is maintained and only in starved individuals muscle protein is used for energy production. The winter feed of the reindeer, the lichens, is poor in nitrogen and the nitrogen balance during winter is strongly negative. Reindeer responds to limited availability of nitrogen by increasing the recycling of urea into rumen. In general the adaptation of reindeer physiology enables the reindeer to survive the winter and although several aspects are known many others require further studies. Abstract in Finnish / Tiivistelmä: Valaistus, lämpötila ja ravinnon saatavuus vaihtelevat vuodenajn mukaan. Jotta nämä muutokset voisivat saada aikaan adaptiivisia muutoksia porossa, ne täytyy muutta hormonisignaaleiksi. Luotettavin näistä edellä mainituista ympäristön vuodenaikaismuutoksista on valo, joka vaikuttaa poron elintoimintoihin käpylisäkkeen ja sen erittämän hormonin, melatoniinin, välityksellä. Melatoniinin plasmapitoisuuksissa on havaittavissa selkeä vuorokausirytmi, joka porolla häviää kesällä ja alkaa uudestaan syksyllä. Melatoniini-hormonin vuodenaikaisvaihtelut ovat mukana säätelemässä lisääntymistä, talvikarvan kasvua, lämmöntuottoa, elopainoa ja immuunitoimintoja. Melatoniini vaikuttaa geeniaktivaation kautta mekanismeilla, joita ei vielä tarkkaan tunneta. Muita hormoneja, joiden erityksessä on havaittu vuodenaikaisvaihtelua, ovat kilpirauhashormonit, insuliini ja leptiini. Havaitut muutokset ovat ilmeisesti usean hormonin yhteisvaikutuksen aiheuttamia. Ruokahalu sekä energian- että lämmöntuotto ovat keskeisiä hengissä säilymisen kannalta. Talvella poron energiatase on negatiivinen ja se käyttää lähinnä varastoimiaan rasvoja energian tuottoon. Rasvojen käyttö on ekonomista, sillä rasvojen hajoaminen, lipolyysi, on säädeltyä ja rasvahappojen käyttö lihaksissa vähenee talvella. Vasta vakavasti nälkiintyneissä poroissa lipolyysi aktivoituu siten, että myös ketoaineita alkaa kertyä vereen. Valkuaisaineiden määrä vähenee vähemmän kuin rasvojen ja ainoastaan nälkiintyneet porot käyttävät lihasten valkuaisaineita energiantuottoon. Poron talviravinnossa, jäkälässä, on vain vähän typpeä, joten talvisin typpitasapaino on voimakkaasti negatiivinen. Poro reagoi tähän vähäiseen typpimäärään lisäämällä urean kierrätystä pötsiin. Kokonaisuudessaan poron elintoimintojen sopeutuminen auttaa poroa selviytymään talven yli. Vaikka adaptaatiosta on joiltakin osin kertynyt runsaasti tietoa, on siinä myös paljon selvitettävää.